2002
DOI: 10.1006/brcg.2001.1481
|View full text |Cite
|
Sign up to set email alerts
|

Left–Right and Upper–Lower Visual Field Asymmetries for Face Matching, Letter Naming, and Lexical Decision

Abstract: The relation between left-right and upper-lower visual field (VF) asymmetries was examined for face matching, letter naming, and lexical decision. Stimuli were flashed in the VF quadrants. Face matching resulted in a lower left and upper right VF advantage. Letter-naming resulted in a distinct upper-right VF advantage. For lexical decision, no upper/lower asymmetries were found. Words were processed faster in the right than in the left VF, while nonwords were processed equally fast in both VFs. The results are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
21
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 21 publications
(38 reference statements)
4
21
2
Order By: Relevance
“…In accordance with the studies showing a lower-upper asymmetry in the visual field (Green et al, 2014;Hagenbeek & Van Strien, 2002;Pitzalis & Di Russo, 2001), we found greater differences in gaze patterns when the trajectories were flipped vertically. The differences between flipped scan patterns were complex, such that a simple overall shift of the flip axis did not reduce differences between groups of scan patterns.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with the studies showing a lower-upper asymmetry in the visual field (Green et al, 2014;Hagenbeek & Van Strien, 2002;Pitzalis & Di Russo, 2001), we found greater differences in gaze patterns when the trajectories were flipped vertically. The differences between flipped scan patterns were complex, such that a simple overall shift of the flip axis did not reduce differences between groups of scan patterns.…”
Section: Discussionsupporting
confidence: 93%
“…These LVF and UVF differences in Drosophila are not an exception. In humans and nonhuman primates, it has been shown that some visual attributes are differentially processed in the LVF and UVF (19,20) and that the attentional resolution is finer in the LVF (21).…”
Section: Discussionmentioning
confidence: 99%
“…There nevertheless are good reasons to believe that reading vertically is less efficient than reading horizontally. Nonreading studies have suggested that oculomotor control is poorer in the vertical than in the horizontal plane (Collewijn, Erkelens, & Steinman, 1988), and that asymmetries in upper-and lower-hemifield sensitivities to visual and linguistic information might impair vertical reading (e.g., Goldstein & Babkoff, 2001;Hagenbeek & Van Strien, 2002;Yu, Legge, Wagoner, & Chung, 2014). However, investigations of reading direction effects in alphabetic languages have been confounded by readers' unfamiliarity with vertical text (Huey, 1898;Schmidt, Ullrich, & Rossner, 1993;Tinker, 1955;Yu, Park, Gerold, & Legge, 2010), and the limited evidence available to date has come from studies with characterbased languages, such as Japanese, that commonly use both horizontal and vertical text formats (Osaka & Oda, 1991).…”
mentioning
confidence: 99%